Fragmentation gradients differentially affect the species range distributions of four taxonomic groups in semi-deciduous Atlantic forest - da Silva, Fernando R.; Rossa-Feres, Denise de Cerqueira [UNESP] (Wiley, 2017)
Human activities often cause habitat fragmentation and how forest fragments affect species range distributions has implications for ecology and conservation. However, few studies have considered communities within the same landscape. Here, we analyzed metacommunity structure to determine the range distributions for species in four taxonomic groups (amphibians, birds, social wasps, and trees) in a patchy landscape of semi-deciduous Atlantic forest in southwestern Brazil. Although trees are a key component of the environment for animals in forested patches, the ranges of bird, wasp, and amphibian species did not change in concert with the species ranges of trees. The species ranges of amphibians and social wasps were unaffected by fragmentation gradients and exhibited independent distribution patterns (i.e., random structure). In contrast, birds and trees exhibited range turnover along different fragmentation gradients, indicating that species show idiosyncratic responses to abiotic factors (i.e., Gleasonian structure). For birds, some less-resilient species occurred only in fragments with a large area of native vegetation at a radius of 5 km from the center of the sampled forest fragments, whereas other more stress-tolerant species occurred only in sites with small areas of native vegetation. For trees, some later succession species (e.g., animal-dispersed seeds) occurred only in fragments with high connectivity, whereas earlier-recruiting species (e.g., wind-dispersed seeds) occurred in fragments with low connectivity. Thus, determining the effects of human-modified landscapes on species range distributions, even within the same landscape, might not be a trivial task.
Keywords: amphibians; birds; Clementsian; Gleasonian; nested; social wasps; trees